Mean-Square Convergence of Two-Step Milstein Methods for Nonlinear Stochastic Delay Differential Equations (Journal of Computational Mathematics, 2026)
In this paper, a numerical method for solving nonlinear stochastic delay differential equations is proposed: two-step Milstein method. The mean square consistent and mean-square convergence of the numerical method are studied. Through the relevant derivation, the conditions that the coefficients need to be satisfied when the numerical method is mean-square consistent and mean-square convergent are obtained, and it is proved that the mean-square convergence order of the numerical method is 1. Finally, the theoretical results are verified by numerical experiments.
Keywords: Stochastic delay differential equation; Two-step Milstein method; Mean-square consistent; Mean-square convergence